Budgeting in Ukraine - Kraan, Dirk-Jan (OECD Publishing, 2013)
This budget review of Ukraine first discusses some general legal, political and economic characteristics of the country and recent institutional reforms. Section 2 examines the budget formulation process with separate attention for the budget structure and classification, the annual budget preparation cycle, medium-term planning, long-term fiscal sustainability, the organisation of the Ministry of Finance, and the funding of local government. Section 3 addresses the parliamentary budget process with special attention for the Budget Committee, the annual parliamentary budget cycle, and the impact of parliament. Section 4 focuses on budget execution with special attention for the annual executive process, cash management, and budgetary discipline. Section 5 looks at the supply side of the budget process: the ministries and agencies that provide for public administration and service delivery at the level of central government, as well as such provision by local governments. Section 5 also addresses public employment, the civil service, public procurement, and the public enterprise sector. Section 6 looks at accounting and audit, with special attention for financial reporting, internal audit, and external audit. JEL classification: H610, H570, H830 Keywords: Budget formulation, budget preparation cycle, budget structure and classification, medium-term planning, long-term fiscal sustainability, parliamentary budget process, parliamentary budget committee, annual budget cycle, budget execution, cash management, budgetary discipline, public administration and service delivery, local government, public procurement, public employment, civil service, public enterprise sector, accounting, audit, financial reporting, internal audit, external audit, Ukraine
Keywords: Finance and Investment; Governance; Ukraine